Development of E-learning Software Based Multiplatform Components - Irma Salamah; M. Aris Ganiardi (Institute of Advanced Engineering and Science, 2017)
E-learning software is a product of information and communication technology used to help dynamic and flexible learning process between teacher and student. The software technology was first used in the development of e-learning software in the form of web applications. The advantages of this technology because of the ease in the development, installation, and distribution of data. Along with advances in mobile/wireless electronics technology, e-learning software is adapted to this technology known as mobile learning. The ability of this electronic device is the same as a single computer even though it is simpler than a single computer. The problem that arises when e-learning software operates on multiple platforms is that computer programs are made repeatedly depending on the platform being used. This situation will obviously affect the quality of e-learning software. To overcome these problems, in this study developed component-based software that is a modern paradigm for software development that produces reusable software components, high quality, and cost-effective. In software development, software components will be assembled in the software in need. The result of this research is high quality e-learning software based multiplatform component.